A systematic review of diet, food, and rehabilitation interventions for chronic musculoskeletal pain in the international classification of functioning, disability, and health (ICF) model - Du, Zihao; Chen, Yukun; Chen, Yuzhi; Rosofsky, Meryl (Progress in Nutrition, 2025)
Background: To evaluate the effects of dietary modifications and specific food choices on chronic musculoskeletal pain management, using the International Classification of Functioning, Disability, and Health (ICF) model to examine their impact on body function, physical activities, and social participation. Methods: This systematic review was conducted from January 2013 to January 2023. A comprehensive literature search across four databases (PubMed, Food Science & Technology Abstracts, ProQuest, and Scopus) yielded 7 randomized controlled trials that met the inclusion criteria. The outcomes measured included pain, inflammation, and quality of life. A Meta-analysis was also employed to explore the overall impact of dietary interventions on pain. Results: Most studies showed significant improvements in pain levels following dietary intervention, with variations depending on the specific dietary modifications. The impact on inflammation, as measured by the Erythrocyte Sedimentation Rate and interleukin levels, presented mixed results. However, a positive effect on quality of life was observed in studies combining dietary interventions with physical therapy or exercise. Conclusion: The results underscore the potential of integrated approaches to chronic musculoskeletal pain management but indicate that further research is needed to clarify the effects on inflammation and identify optimal dietary strategies for different pain conditions.